Pertanggungjawaban dan Akibat Hukum Penyalahgunaan Kewenangan Direksi Perseroan Terhadap Penjualan Aset Perusahaan - Ghina Mahira, Nadhila (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
Purpose of this study is as a requirement for graduation and get Master of Notary at the Faculty of Law, University of Surabaya. Practical purpose of this study was intended to determine whether the actions of directors in selling the company's assets that result in harm to the company can cause harm to a third party acting in good faith as a buyer. The results of the study addressed that, that the Board of Directors of the BM can act detrimental LA because, as the United States Director of BM has made disbursements Giro owned LA without first doing the backfill soil. This is not in accordance with the agreement between the LA with the United States in accordance with Article 3 of the Sale and Purchase Agreement (CSPA) No. 26, 28, and 30, respectively on 12 December 2011 There is a conflict of interest. LA as a buyer is the brother-in-law of the United States, so there has been a violation of Article 99 paragraph (1) Member of the Company Law which states that the Board of Directors is not authorized to represent the Company if a conflict of interest with the Company. Pursuant to Article 102 paragraph (4) of the Company Law, LA as the buyer can prove the existence of good faith at the time of purchasing the land LA, so LA will still be protected by law. Based on this study it is suggested discussion Should for any company who is a Limited Liability Company, if will take legal action, all Directors and staff with a true and deep understanding of the procedures or processes to the sale and purchase of any asset, for example the General Meeting of Shareholders held Extraordinary (EGM) which produce a binding agreement, so there will be no abuse of power. Company Law should further clarify the criteria of good faith by the Board of Directors to be done. There should be a legislation that explicitly states the criteria for a good faith purchaser. Keywords: Abuse of Authority; Directors; Of Peddling Corporate Asset.